2022
DOI: 10.1007/s11469-021-00750-5
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Over Time and Financial Concerns Predict Change in Online Gambling During COVID-19

Abstract: This study examined online gambling behavior during COVID-19 land-based gambling restrictions and associations with changes in mental health, impacts on household income due to the pandemic, financially focused motivations, and symptoms of gambling problems. A repeated online survey was administered to adult gamblers in Ontario, Canada. Wave 1 was conducted at the beginning of the first COVID-19 lockdown (April 2020) and wave 2 in August 2020. Respondents (N = 940) completed validated self-report questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…Individuals who gambled during heightened restrictions reported stronger symptoms of depression and anxiety; mean scores on the PHQ-4 were 5.83 vs 2.63 (p<0.001). There were similar findings in Canada ( Price et al 2022 ) and Italy ( Lugo et al 2021 ). Of the studies that found marginal or no impacts of gambling on mental health, no relationship between anxiety and gambling frequency was found in a UK-based study (Emond et al 2021) and the use of gambling-related advice, support and treatment remained largely unchanged during the first year of the pandemic ( Gunstone et al 2020 ).…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…Individuals who gambled during heightened restrictions reported stronger symptoms of depression and anxiety; mean scores on the PHQ-4 were 5.83 vs 2.63 (p<0.001). There were similar findings in Canada ( Price et al 2022 ) and Italy ( Lugo et al 2021 ). Of the studies that found marginal or no impacts of gambling on mental health, no relationship between anxiety and gambling frequency was found in a UK-based study (Emond et al 2021) and the use of gambling-related advice, support and treatment remained largely unchanged during the first year of the pandemic ( Gunstone et al 2020 ).…”
Section: Resultssupporting
confidence: 75%
“…Similarly in the US, amongst 424 participants who had previously gambled, there was a significant decrease in online gambling but 8% of this sample who had not previously gambled did so for the first time after the onset of COVID-19 ( Xuereb et al 2021 ). Gambling behaviours may have been negatively impacted amongst specific cohorts; Emond et al (2021) and Price et al (2022) found that online gambling increased for groups of occasional or regular gamblers.…”
Section: Resultsmentioning
confidence: 99%
“…The studies indicate a link between change in online gambling involvement during COVID-19 and increased mental health problems (Price et al, 2022), including stress from boredom (Fluharty et al, 2022), and higher levels of depression and anxiety (Fluharty et al, 2022;Price et al, 2022).…”
Section: Risk Factors For Increased Online Gambling During Covid-19mentioning
confidence: 96%
“…During 2020/21 almost one-quarter of online gamblers increased their gambling during lockdown (Bellringer & Garrett, 2021;Fluharty et al, 2022;Swanton et al, 2021), with this most likely to be on overseas gambling sites, instant scratch card gambling and Lotto (Bellringer & Garrett, 2021;Price et al, 2022). The sociodemographic risk factor for increased online gambling was higher education (Bellringer & Garrett, 2021), or low education (Fluharty et al, 2022), and financial difficulties related to COVID (Price et al, 2022;Swanton et al, 2021).…”
Section: Risk Factors For Increased Online Gambling During Covid-19mentioning
confidence: 99%
“…The COVID-19 pandemic can be regarded as a major external stressor (Price et al, 2022 ). Due to the major negative effects of the pandemic to the economy (Fernandes, 2020 ), employment (Zhang et al, 2020 ) and mental health (Dsouza et al, 2020 ), the pandemic effects are distinct from other types of stressors that have been discussed in previous SRD studies.…”
Section: Study 2: Literature Review and Hypothesis Developmentmentioning
confidence: 99%